The Profile of Mortality Among Healthcare Workers in Indonesia due to Covid-19 - Yuniasih, Dewi Yuniasih; Ghifari, Ahmad; Hasanah, Murtafiqoh; Permana, Iman (Faculty of Medicine Universitas Sebelas Maret, 2022)
Background: The increasing number of people infected with Covid-19 worldwide has brought many countries to the next wave of this pandemic. Indonesia was estimated to face the third wave in early 2022 unless active precautions were put into action. Healthcare workers (HCWs) are the essential frontline in the effort to minimize the spreading of the disease. Nevertheless, HCWs are amongst the casualties of the disease, especially in Indonesia, which is regarded as among the countries with the highest HCW mortality. This study aims to describe the mortality rates of HCWs in Indonesia.Methods: The retrospective data were obtained from the official website of LaporCovid, an independent Indonesian initiative to provide information regarding Covid-19, to obtain secondary data following the research objectives.Results: Our study found that 1,551 health workers in Indonesia died from Covid-19 until 25 July 2021, and almost one-third of them were doctors. Furthermore, East Java is the most prevalent province and only one province (out of 33) has not reported causality.Conclusions: The second wave of the pandemic has overwhelmed health workers and has become infected and eventually many health workers have died more than in the previous months.